More Than One-third of Orthopaedic Applicants Are in the Top 10%: The Standardized Letter of Recommendation and Evaluation of Orthopaedic Resident Applicants. Issue 8 (August 2021) - Pacana, Matthew J.; Thier, Zachary T.; Jackson, J. Benjamin; Koon, David E.; Grabowski, Gregory
Abstract: Background: The American Orthopaedic Association (AOA) released the standardized letter of recommendation (SLOR) form to provide standardized information to evaluators of orthopaedic residency applicants. The SLOR associates numerical data to an applicant's letter of recommendation. However, it remains unclear whether the new letter form effectively distinguishes among orthopaedic applicants, for whom letters are perceived to suffer from "grade inflation." In addition, it is unknown whether letters from more experienced faculty members differ in important ways from those written by less experienced faculty. Questions/purposes: (1) What proportion of SLOR recipients were rated in the top 10th percentile and top one-third of the applicant pool? (2) Did letters from program leaders (program directors and department chairs) demonstrate lower aggregate SLOR scores compared with letters written by other faculty members? (3) Did letters from away rotation program leaders demonstrate lower aggregate SLOR scores compared with letters written by faculty at the applicant's home institution? Methods: This was a retrospective, single institution study examining 559 applications from the 2018 orthopaedic match. Inclusion criteria were all applications submitted to this residency. Exclusion criteria included all letters without an associated SLOR. In all, 1852 letters were received; of these, 26% (476) were excluded, and 74% (1376) were analyzed for SLOR data. We excluded 12% (169 of 1376) of letters that did not include a final summative score. Program leaders were defined as orthopaedic chairs and program directors. Away rotation letters were defined as letters written by faculty during an applicant's away rotation. Our study questions were answered accounting for each subcategory on the SLOR (scale 1-10) and the final ranking (scale 1-5) to form an aggregated score from the SLOR form for each letter. All SLOR questions were included in the creation of these scores. Correlations between program leaders and other faculty letter writers were assessed using a chi-square test. We considered a 1-point difference on 5-point scales to be a clinically important difference and a 2-point difference on 10-point scales to be clinically important. Results: We found that 36% (437 of 1207) of the letters we reviewed indicated the candidate was in the top 10th percentile of all applicants evaluated, and 51% (619 of 1207) of the letters we reviewed indicated the candidate was in the top one-third of all applicants evaluated. We found no clinically important difference between program leaders and other faculty members in terms of summative scores on the SLOR (1.9 ± 0.7 versus 1.7 ± 0.7, mean difference -0.2 [95% CI -0.3 to 0.1]; p < 0.001). We also found no clinically important difference between home program letter writers and away program letter writers in terms of the mean summative scores (1.9 ± 0.7 versus 1.7 ± 0.7, mean difference 0.2; p < 0.001). Conclusion: In light of these discoveries, programs should examine the data obtained from SLOR forms carefully. SLOR scores skew very positively, which may benefit weaker applicants and harm stronger applicants. Program leaders give summative scores that do not differ substantially from junior faculty, suggesting there is no important difference in grade inflation between these faculty types, and as such, there is no strong need to adjust scores by faculty level. Likewise, away rotation letter writers' summative scores were not substantially different from those of home institution letters writers, indicating that there is no need to adjust scores between these groups either. Based on these findings, we should interpret letters with the understanding that overall there is substantial grade inflation. However, while weight used to be given to letters written by senior faculty members and those obtained on away rotations, we should now examine them equally, rather than trying to adjust them for overly high or low scores. Level of Evidence: Level III, therapeutic study.